Conversational Implicature Used in Gone Girl Movie Script by Gillian Flynn - Sharma, R.B.; Yanti, Novi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
The purpose of this study is to describe the implied meaning of conversational implicatures found in the film Gone Girl. The method used in this research is content analysis with the object of study on conversational implicatures in film dialogue. The technique used is note-taking. Based on the results of the study, it was found that the most frequent maxim found by the writer is the maxim of quantity in which it means that the characters in the movie failed to observe it as the contribution of the information is insufficient and less-informative than it is required. After that, it is followed by the maxim of manner in which it means the characters of the movie failed to observe, consequently it creates the sense of ambiguity and proximity. Then, the maxim of relation in which it shows that the characters of the movie give irrelevant information. Lastly, there is maxim of quality in which that means the characters of the movie failed to notice due to false information.